2017
DOI: 10.1007/s10815-017-0883-9
|View full text |Cite
|
Sign up to set email alerts
|

Morbid obesity and pregnancy outcomes after single blastocyst transfer: a retrospective, North American study

Abstract: Morbid obesity is a strong and independent predictor of poor pregnancy outcomes in patients undergoing top-quality SBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…However, recent studies have shown no association between vitamin D levels and ovarian reserve, ovarian response, or pregnancy rates [34][35][36]. Finally, although BMI was controlled for in our study, it is possible for obesity to be an independent mediator of lower ovarian reserve, ovarian response, and pregnancy rates in ICSI-ET cycles [37][38][39].…”
Section: Discussioncontrasting
confidence: 55%
“…However, recent studies have shown no association between vitamin D levels and ovarian reserve, ovarian response, or pregnancy rates [34][35][36]. Finally, although BMI was controlled for in our study, it is possible for obesity to be an independent mediator of lower ovarian reserve, ovarian response, and pregnancy rates in ICSI-ET cycles [37][38][39].…”
Section: Discussioncontrasting
confidence: 55%
“…Studies on single-embryo transfers showed that obesity was negatively associated with the occurrence of live birth [24]. A retrospective study found that morbid obesity significantly increased miscarriage rates and reduced live birth rates [25]. However, in contrast to our research, their study included only blastocyst transfer and fresh and frozen embryos.…”
Section: Discussionmentioning
confidence: 58%
“…In the final analysis, 105 eligible studies (19 prospective and 86 retrospective cohort studies) were included, involving more than 271,632 pregnant women (Figure 1). 14,15,28–130 The main characteristics of included studies were summarized in Table S1. In total, 100 studies reported the association between maternal BMI and CPR among pregnant women undergoing ART, among which 53 reported MR and 51 reported LBR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 100 studies reported the association between maternal prepregnancy body weight and CPR after ART 14,15,28–55,58–80,82–117,119–122,124–130 . At per‐woman level, 54 studies, involving 109,688 pregnant women, showed an inverted J‐shaped relationship between maternal BMI and CPR ( P n < 0.01) 14,28–31,34–36,40,41,44,46,47,49,53,58,60,61,64–68,75,76,78,82,85,86,88–95,97,99,103–106,109,112–114,119,121,124,126–128,130 . Compared with the reference BMI value (21.75 kg/m 2 ), BMI > 22.5 kg/m 2 was associated with lower CPR (Figure 2a and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation